EFL Learners’ Problems and Opportunities During Emergency Remote Teaching - Nawwaratul Fahriyah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Emergency Remote Teaching (henceforth, ERT) is a learning concept that utilizes electronic media. According to Hodges et al. (2020), ERT can be applied in conditions where the teaching and learning process cannot be carried out directly (face-to-face learning) due to crisis circumstances, e.g., a crisis of the spread of viruses or a crisis of natural disasters. Some research has been conducted to investigate an ERT from different sides. Moreover, as far as the researcher has explored, there are some studies related to problems and opportunities that focus on university students’ experiences in an Indonesian setting. However, there is a notable gap in studies addressing the specific problems and opportunities faced by university students, particularly those studying English as a Foreign Language (EFL), within an Indonesian context. Further, some research is needed to find the biggest problems and opportunities of ERT, focusing on the experiences of EFL learners at the university level, so that might help them minimize the worst possible outcomes. The design of this research was a survey study design. It employed simple random sampling as the sampling method and obtained 96 active student representatives of the English education study program from the class of 2018 to 2021, taken from 20% of each school generation. The questionnaire was adapted from the advantages and disadvantages of an e-learning questionnaire developed by Baczek et al., (2021), which was assessed by the Bioethics Committee. The questionnaire was divided into three parts, the first part was given to obtain detailed information about the participants; the second part consisted of 12 statements about the problems of ERT; and the last part consisted of 10 statements about the opportunities of ERT. The results of the reliability and validity test showed that Pearson's correlation coefficients for each item of the questionnaire, either problems and opportunities of ERT were valid and had acceptable consistency. The result of the biggest EFL learners’ problems during ERT has shown that online classes reduce the interaction between lecturers and students. It showed that over 50 participants or 52% expressed their agreement with additional 30 (31%) responded with strong agreement. Therefore, a majority of participants specifically over 80 participants or 83% marking it as the predominant viewpoint on this topic according to the survey results. As Baczek et al., (2021), poor interaction between learners and facilitators, and a lack of clarity about the purpose and goals of learning can impede the learning process. Based on the result of the biggest EFL learners’ opportunities during ERT has shown that the biggest opportunity during ERT was that Lecturers and students utilized group chat, forums and virtual meetings (Zoom Meeting/Google Meet) in making interaction for online learning, which refers to classes interactivity, it gained a very high score (89%). It showed that over 52% of students agreed and 31% strongly agreed with the statement. According to the data, the use of applications in interactions between lecturers and students can be an opportunity that can help them communicate about learning material. That is a great way to foster online learning and interaction by using these tools, lecturers and students can build a sense of community and collaboration, despite the physical distance, and make the learning experience more engaging and effective (Lestari et al., 2021).
Reupload File Repositori 24 Februari 2026_Teddy/Hendra
Keywords: EFL; Teaching; Emergency